2011
DOI: 10.1007/s12070-011-0258-y
|View full text |Cite
|
Sign up to set email alerts
|

The MicroFlow Spacer: A Drug-Eluting Stent for the Ethmoid Sinus

Abstract: To evaluate the short-term outcomes and safety of a newly introduced drug-eluting ethmoid stent. Prospective study of 23 patients with a total of 40 implanted ethmoid sinuses. Two tertiary care medical facility. Twenty-three patients with medically refractory chronic rhinosinusitis were treated with patient-appropriate endoscopic sinus surgery, with the modification of treating the ethmoid sinuses with an ethmoid stent infused with triamcinolone, instead of conventional endoscopic ethmoidectomy. Patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…No complications were encountered and it was recommended that insertion of the Stratus Spacer into the ethmoid sinuses should be used with C-arm fluoroscopy for novice users. 11 …”
Section: Discussionmentioning
confidence: 99%
“…No complications were encountered and it was recommended that insertion of the Stratus Spacer into the ethmoid sinuses should be used with C-arm fluoroscopy for novice users. 11 …”
Section: Discussionmentioning
confidence: 99%
“…They are intended to fill the ethmoid sinus cavity, which would otherwise be filled with blood and mucous [ 63 ]. Examples of clinically approved middle meatal implants include Propel™ implant [ 72 ], Relieva Stratus™ MicroFlow spacer [ 73 ] and the Sinu-Foam™ spacer [ 74 , 75 ].…”
Section: Clinical Applications Of Drug-eluting Nasal Implantsmentioning
confidence: 99%
“…This device is temporary requiring manual removal after 30 days and a new device may be implanted if needed [ 83 ]. This device also is not suitable for patients with extensive polyps [ 73 ]. Finally, certain adverse events have been reported for the device [ 81 ] and orbital violation following its placement has been reported [ 84 ].…”
Section: Clinical Applications Of Drug-eluting Nasal Implantsmentioning
confidence: 99%
“…The device is approved for saline, however, in an attempt to deliver corticosteroid, physicians have placed triamcinolone into the device reservoir. Investigations have revealed that the device eludes 0.3 ml of triamcinolone acetate 40 mg/ml over 2 to 4 weeks 91 . Approved by the FDA in 2011, the Propel sinus implant (Intersect ENT, Palo Alto, California) is a newer bioabsorbable implant that self-expands in the sinus cavity and releases 370 µg of mometasone furotate over 4 weeks 92 .…”
Section: New and Future Directionsmentioning
confidence: 99%